Evaluation of liver function by means of serum cytokeratin 18 and hepatocyte growth factor levels in patients with obstructive jaundice - Ozturk, Nurinnisa; Ozturk, Gurkan; Cerrah, Serkan; Atamanalp, Sabri Selcuk; Gul, Mehmet Ali; Aksungur, Nurhak; Bakan, Nuri; Bakan, Ebubekir (Acta chirurgica belgica, 2018)
To evaluate the serum levels of cytokeratin 18 (CK18) and hepatocyte growth factor (HGF) in obstructive jaundice patients before and after treatment and thereby to detect the possible role of CK18 and HGF in patients with obstructive jaundice. Forty patients who had obstructive jaundice and 40 healthy control subjects were included in the study. Patients were treated using percutaneous, endoscopic or surgical approaches. Blood samples were obtained at the day before and 7 days after the intervention for obstructive jaundice. Serum HGF and CK18 concentrations were determined by ELISA method. There were statistically significant decreases in HGF, CK18, total bilirubin and direct bilirubin serum levels, aspartate aminotransferase, alanine aminotransferase, gamma-glutamyltransferase, and alkaline phosphatase activities and white blood cell count when compared with pre-treatment levels. Evaluating pre- and post-treatment serum HGF and CK18 levels suggested that there was an apoptosis in obstructive jaundice patients and this apoptosis decreased after the decompression of the biliary tract. We also demonstrated that HGF levels were altered at biliary obstruction compared to healthy controls and the levels of this biomarker also decreased after decompression of biliary obstruction. We concluded that these biomarkers can be used as predictors of liver injury in biliary obstruction.